Soil erosion by assessing hydrothermal conditions of its formation - A.B. Achasov; A.A. Achasova; A.V. Titenko (Global Journal of Environmental Science and Management)
Soil erosion is one of the vital factors contributing to the loss of fertility and environmental degradation. Generally accepted diagnostics of eroded soils is based on comparison of the sloping soils profile depth with the watershed soils. In this case, there is a separate problem of slope soils with a naturally shortened profile and eroded soils. Formation of the soil’s natural profile on the slopes, caused by the action of natural factors of soil formation, can be described using a mathematical model, characterizing hydrothermal conditions of the slope areas through relative parameters of insolation (Ki) and moisture. These parameters describe the difference in soil formation conditions on the slopes from the upland areas. They are calculated based on the landforms parameters – incline and slope exposure. Their ratio, xeromorphy coefficient, can be used to forecast humus content and profile thickness of non-eroded soils on the slopes. As studies have shown, for non-eroded chernozem soils of Ukraine, the parameter xeromorphy describes 49% of the profile thickness dispersion, while for eroded soils it does not depend on this parameter. Thus, this model of profile thickness P versus xeromorphy can be used to forecast the thickness of non-eroded soil for specific conditions. Deviation of the profile thickness from the forecast one can be considered as the manifestation of erosion or denudation.